Immediate postpartum intrauterine contraceptive device insertions in caesarean and vaginal deliveries: a comparative study - Goyal, Ritu; Bedi, Mini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Post-partum family planning is prevention of unintended and closely spaced pregnancies during first 12 months following childbirth. Postpartum IUCD is the best method of all as it is the safest, most effective, has no effect on breast feeding, reliable and with minimum complications. Methods: The cross-sectional study was conducted in AIMSR Bathinda on 400 postpartum patients. It was a prospective, observational study of women who received PPIUCD in our region. Results: Out of total 400, 58% had normal vaginal delivery and 42% had cesarean section. PPIUCD was done in all cases after applying exclusion criteria and the females were called for follow up. 53% cases who had cesarean and 47% of normal vaginal delivery turned up for follow up. Acceptance is more in multipara (20.7%) than in primi patients (13.7%). Almost 90% patients had good continuation rate. There were few problems faced by patients like irregular bleeding for first few months, pain lower abdomen, leucorrhea etc. which were removed by good counseling and some treatment like NSAIDs for bleeding. Conclusions: The acceptance of PPIUCD was high in present study in both types of females delivered by normal vaginal delivery or post LSCS but with good counseling efforts. It was safe and effective and had high retention rate when done at good timing by trained service provider that is within 10 minutes of placental delivery. So the need of time is creating awareness of public towards it and removing fear from minds, breaking taboos and myths.